Synchronous Upper GIT Malignancy in an Elderly Patient - Islam, M M Shahin Ul; Sarker, Mst Naznin; Jannat, Syeda Nur E; Das, Nimai; Hossain, Mohammad Iqbal; Mondal, Swapan Kumar; Rahman, ATM Ataur; Ahmed, Dewan Saifuddin (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Previously thought that, synchronous colonic cancers are relatively common but synchronous upper gastrointestinal cancers are relatively uncommon. But now a days, frequency of synchronous esophageal cancers, gastric cancers or duodenal cancers is increasing due to availability of the upper GI endoscopy, and the prolonged life span of the general population. Here we discussed anelderly malewho presented with features of gastric outlet obstruction and dysphagia and finally diagnosed as simultaneous esophageal squamous cell carcinoma and gastric adenocarcinoma. Bangabandhu Sheikh Mujib Med. Coll. J. 2022;1(2):107-109